The Effect of Mindfulness Meditation on Nursing Students’ Stress and Anxiety Levels - Ady Irawan. AM; Anggie Pradana Putri; Mheru Nisha; Agung Widiastuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nursing students often face significant stress and anxiety, impacting their cognitive function, academic performance, and clinical skills. Effective interventions to support their mental health are needed. This study investigates the effect of an eight-week mindfulness meditation course on stress and anxiety levels of nursing students during clinical placements. Conducted from February to May 2024 at nursing schools in Surakarta, Indonesia, the quasi-experimental study included 35 students who attended weekly 50-minute mindfulness sessions. The Five Facet Mindfulness Questionnaire (FFMQ), Zung Self-Rating Anxiety Scale (Zung-SARS), and Beck Depression Inventory (BDI) were administered at baseline (T0), post-intervention (T1), and four weeks post-intervention (T2). Results showed significant improvements in mindfulness, with FFMQ scores increasing by 11.43 from T0 to T1 (p < 0.001) and by 10.86 from T0 to T2 (p < 0.001). Anxiety and depression levels significantly decreased, with Zung-SARS scores dropping by -6.89 from T0 to T1 (p < 0.001) and -7.08 from T0 to T2 (p < 0.001), and BDI scores decreasing by -5.89 from T0 to T1 (p < 0.001) and -5.86 from T0 to T2 (p < 0.001). The study suggests mindfulness meditation can significantly enhance mental health among nursing students.